2022
DOI: 10.3390/fib10060053
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Hybrid Steel-Polypropylene Fiber Reinforced High Strength Concrete Exposed to Various Temperatures

Abstract: Combining different types of fibers inside a concrete mixture was revealed to improve the strength properties of cementitious matrices by monitoring crack initiation and propagation. The contribution of hybrid fibers needs to be thoroughly investigated, taking into consideration a variety of parameters such as fibers type and content. In this paper, the impact of integrating hybrid steel-polypropylene fibers on the mechanical properties of the concrete mixture was investigated. Hybrid fiber-reinforced high-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…It can be computed by dividing the ultimate deformation that occurs at the ultimate shear force by the cracking deformation that occurs at the cracking shear force (Pakravan et al, 2016;Yan et al, 2021). The fact that when the hybrid fibers were added, the cracking and ultimate shear strengths increased supports their ability to withstand macro and micro cracks at different stress levels, delaying the cracking process and improving stiffness and strength (Tahenni et al, 2016;Sivakumar et al, 2020;Ismail and Hassan, 2021;Shaaban et al, 2021;Yang et al, 2021;Tawfik et al, 2022). The increase in ultimate deformation and ductility values is a further indication of the efficacy of hybrid fibers in reducing concrete's brittleness and improving its capability for plastic deformation without fracture.…”
Section: Effect Of Using Hybrid Polypropylene-steel Fibersmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be computed by dividing the ultimate deformation that occurs at the ultimate shear force by the cracking deformation that occurs at the cracking shear force (Pakravan et al, 2016;Yan et al, 2021). The fact that when the hybrid fibers were added, the cracking and ultimate shear strengths increased supports their ability to withstand macro and micro cracks at different stress levels, delaying the cracking process and improving stiffness and strength (Tahenni et al, 2016;Sivakumar et al, 2020;Ismail and Hassan, 2021;Shaaban et al, 2021;Yang et al, 2021;Tawfik et al, 2022). The increase in ultimate deformation and ductility values is a further indication of the efficacy of hybrid fibers in reducing concrete's brittleness and improving its capability for plastic deformation without fracture.…”
Section: Effect Of Using Hybrid Polypropylene-steel Fibersmentioning
confidence: 99%
“…Additionally for the significance of these fibers in enhancing concrete's behavior in resisting tensile stresses and minimizing the formation and propagation of cracks. The findings of earlier studies demonstrated that utilizing hybrid fibers enhanced concrete strength and durability as well as minimized cracks compared to using a single type of fiber (Hoang and Fehling, 2017;Li et al, 2018;Zhang et al, 2018;Ali et al, 2020;Sivakumar et al, 2020;Zhong et al, 2020;Tawfik et al, 2022). Tawfik et al (2022) observed that using hybrid fibers rather than only one kind of fiber increased the strength of the composite in terms of compressive, flexural, and tensile stresses by 50%, 46%, and 53%, respectively.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The study of concretes containing fibers shows, in the presence of polypropylene, a decrease in the vapor pressure peak with the rise in temperature. This decrease is related to the volume of fibers [12][13][14][15]. The study of the influence of metal fibers on the behavior of concrete brought to high temperature shows for some authors a thermal instability at low temperature (below 200 • C) or delayed instability (from 800 • C) [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Several parameters may be at the origin of the observed differences: the mode of hardening of the specimens (dry or saturated specimens); the heating rate; and the fiber content, which seems to be a preponderant factor [18]. The high quantity of fibers can also generate an additional thermal gradient, which would lead to the phenomenon of thermal instability [12,14].…”
Section: Introductionmentioning
confidence: 99%